Conservation priorities of Indian goat breeds based on genetic and non-genetic parameters - SAH, RAJKUMAR; DIXIT, SAT PAL (The Indian Journal of Animal Sciences, 2021)
Indian goats have unique characteristics in terms of production, reproduction, disease resistance and adaptability in different agro-climatic regions of the country. Since, the country has vast goat genetic resources and different climatic regions but limited facilities including fund, there is a need for setting priority for conservation and better utilization. The microsatellite data of 1237 random DNA samples on 25 markers as well as morphological/ demographic information pertaining to 27 goat breeds/populations were used to study the extinction probability and conservation priority based on different approaches. Extinction probability based on census and microsatellite data revealed same order of priority for conservation in >50% cases. Surti, Zalawadi and Gaddi were at higher risk of extinction probability (â‰¥0.63) and more than half of the Indian goat breeds were having <50% extinction probability. The study will help to manage goat genetic resources of the country and to conserve suitable breeds of goat.